1995
DOI: 10.1111/1523-1747.ep12613587
|View full text |Cite
|
Sign up to set email alerts
|

Human Dermal Endothelial Cells Express Membrane-Associated Mast Cell Growth Factor

Abstract: Mast cell growth factor (MGF), a molecule that serves as a ligand for the receptor tyrosine kinase c-kit, is important in mast cell differentiation, migration, and activation. Previous studies of paraffin-embedded human skin using antibody to murine MGF and reverse transcription-polymerase chain reaction have demonstrated MGF protein and mRNA expression in keratinocytes and isolated dermal cells. We utilized a monoclonal antibody to human MGF to further define patterns of immunoreactivity in frozen specimens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…28,29) Previous studies suggested that SCF/ KIT signaling is involved in the mechanism of melanocyte migration, such as melanocyte migration from the neural crest into the epidermis, 30) melanocyte distribution in the hair follicle during fetal development, 31) melanocyte migration in chemotherapy-induced hair loss 32) and increased migration of melanocytes into the epidermis caused by local SCF injection. 33) In vitro, SCF stimulates epidermal melanocyte chemokinesis and increases the speed of melanocyte movement on FN-coated dishes, 21,34) but the effect of SCF on MPs migration was unknown.…”
Section: Fig 3 the Regulatory Effect Of Scf On Mps Adhesion To Matrmentioning
confidence: 99%
“…28,29) Previous studies suggested that SCF/ KIT signaling is involved in the mechanism of melanocyte migration, such as melanocyte migration from the neural crest into the epidermis, 30) melanocyte distribution in the hair follicle during fetal development, 31) melanocyte migration in chemotherapy-induced hair loss 32) and increased migration of melanocytes into the epidermis caused by local SCF injection. 33) In vitro, SCF stimulates epidermal melanocyte chemokinesis and increases the speed of melanocyte movement on FN-coated dishes, 21,34) but the effect of SCF on MPs migration was unknown.…”
Section: Fig 3 the Regulatory Effect Of Scf On Mps Adhesion To Matrmentioning
confidence: 99%
“…In the skin, SCF is synthesized by fibroblasts, keratinocytes, Langerhans cells, mast cells and endothelial cells (79,155). SCF promotes the survival, proliferation, differentiation and maturation of mast cells, and it induces and/or enhances their mediator release, chemotaxis, adhesion and migration (10,(155)(156)(157).…”
Section: Ngfmentioning
confidence: 99%
“…54 Activation of integrins by cytokines, such as SCF, can result in enhanced binding of integrins to their cognate ligands, and these changes contribute to an integrated signal for coordinated cellular events such as directed cell migration. Since SCF is expressed by endothelial cells, 55,56 it is likely to cooperate with integrins in modulating biologic responses in circulating mast cells. This was recently illustrated by means of a coculture system in which proliferation of mast cells was shown to be dependent on the cooperation between c-Kit and ␣ 4 ␤ 1 integrins on mast cells and VCAM-1 and SCF on HUVEC cells.…”
mentioning
confidence: 99%